Bentuk Numeralia 1--10 dalam Bahasa-Bahasa Daerah di Kabupaten Kepulauan Yafen - Buha Aritonang (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2017)
Numeralia are not as easy as counting one, two, three, and so on and its form in every language is different. The purpose of this studi was to discribe numeral forms 1 to 10 in the regional languages of Yfen Island district. The research was condukted in 12 different villages who has different language.The research method was using qualitative method.The result of this ressearch are (1) numeralia form from 1--10 is classified into (a) basic numeralia such as number from 1--5 in Ambai's, Saweru's, Yawa Onate's, Serui Laut's, Warari Onate's, Busami's, Marau's, Munggui's, Ansus-Papuma's, Poom's, Wabo's, and Wooi Dumani's langauge; number 6-7 in Ambai language; dan 6—9 in Marau's, Munggui's, Ansus-Papuma's, Poom's, Wabo's, dan Wooi Dumani's and (b)combined numeralia such as 8 and 9 in Ambai's dan 6—9 Saweru's, Yawa Onate's, Serui Laut's, and Warari Onate's; (ii) some of the derived numeralia in Yapen Isle local languages use linker rei/iji for add such as six in Saweru's dan Yawa's; (iii) linker ko 'add' is an important part to combine the derived numeralia from muner 6--9; (iv) derived numeralia has no linker if it describe number 6-9 in Warari Onate's, and (v) combined numeralia could be in the form of reduction such as number 10 in Ambai Language.